Colistin Resistant A. baumannii: Genomic and Transcriptomic Traits Acquired Under Colistin Therapy - Cafiso, Viviana; Stracquadanio, Stefano; Lo Verde, Flavia; Gabriele, Giacoma; Mezzatesta, Maria Lina; Caio, Carla; Pigola, Giuseppe; Ferro, Alfredo; Stefani, Stefania (Frontiers in Microbiology, 2019)
Despite the fact that colistin-based treatment represents the antimicrobial-regimen backbone for the management of multidrug-resistant Gram-negative infections, colistin resistance is still rare in Acinetobacter baumannii (Ab). We investigated the genomics and transcriptomics of the two clinical Extensively Drug Resistance (XDR) colistin-susceptible/resistant (COL-S/R) pairs of Ab strains in which COL-resistance developed after exposure to colistin therapy. The molecular and genomic explication of these strains highlighted that Ab strains were PFGE-A, ST-281, OXA-23 producers, resistant to imipenem, meropenem, ampicillin/sulbactam, ciprofloxacin, gentamicin, amikacin, and trimethoprim/sulfamethoxazole, susceptible to tigecycline, and the NGS resistome confirmed their XDR genotype. Mapping on Ab ATCC 17978 and Ab ACICU reference genomes, comparative genomics of the isogenic COL-R vs COL-S Ab strains revealed distinctive genomic SNPs accumulated in hotspots including proB gene, genes encoding porins and surface adhesion proteins in the two COL-R Ab strains. Furthermore, a non synonymous SNP in pmrB determining the L208F AA change in COL-R Ab 1-R and a non-synonymous SNP leading the PmrB R263H substitution in COL-R Ab 2-R were found. Notably we recovered for the first time lpxC and lpxD SNPs, previously described only in "in-vitro generated" mutants and associated with colistin resistance, in the clinical COL-R Ab 1-R isolate. COL-R vs COL-S transcriptomics evidenced the over-expression of seven transcripts encoding the PgaB lipoprotein implicated in the polysaccharide metabolism involved in biofilm matrix production, the diacylglycerol kinase for the lipid recycling in the membrane derived oligosaccharides cycle, a membrane no-ribosomal peptide synthetase, the Lipid A phosphoethanol aminotransferase PmrC, and three hypothetical proteins. The transcript analysis of the "COL-R related genes" and the RNA-seq data confirmed that a pmrCAB over-expression with a greater positive net cell-charge and a lpxACD down-regulation in COL-R with decreased LPS as main mechanisms of colistin-resistance. Our study reports the COL-R Ab genomic and transcriptomic signatures reflecting the interplay between several direct and indirect potential adaptations, including the occurrence of hotspot loci of SNP accumulation in genes related to intrinsic colistin-resistance, surface adhesion proteins and porins, and an over-expression of genes involved in different pathways, i.e. biofilm production, oxidative stress response, extensive drug resistance, and colistin-resistance.